Expressive Illocutionary Acts Found in Paw Patrol: The Movie 2021 - Agung Ayu Dian Mahadewi, Anak; Ayu Putri Gita Ardiantari, Ida (CV. Multi Kreasi Media, 2024)
− The research aimed to identify the occurrence of expressive illocutionary acts in the movie Paw Patrol: The Movie 2021 and to explore their types and intentions within the context provided. It utilized the framework proposed by Searle & Vanderveken (1985) and employed a descriptive qualitative approach to analyze the data. Both formal and informal methods were utilized to present the data, incorporating discussions and outcomes. The analysis revealed a total of 122 instances of expressive illocutionary acts in the movie, with protesting emerging as the most prevalent expression, constituting 25% of the acts with 31 utterances. In this study, 9 of the 12 expressive illocutionary acts were examined, including apologize 9%, thank 10%, condole 2%, complaint 10%, protest 25%, boast 10%, compliment 6%, praise 13%, and greet 15%.